2015
DOI: 10.3904/kjim.2015.30.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for endogenous endophthalmitis in patients with pyogenic liver abscesses

Abstract: Background/AimsAlthough pyogenic liver abscesses (PLAs) can be successfully treated, the visual prognosis of patients with endogenous endophthalmitis (EE) associated with a PLA is poor. Early diagnosis and prompt intervention may salvage useful vision. Therefore, we investigated risk factors for EE in patients with PLA, to facilitate early diagnosis.MethodsData from 626 patients diagnosed with PLA between January 2004 and July 2013 were analyzed retrospectively. Patients were divided into two groups: those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Although it is caused by hematogenous spread, endogenous endophthalmitis tends to develop unilaterally, with the right eye more commonly affected, possibly due to the more proximal and direct arterial route from the heart to the right carotid artery. Several risk factors for endogenous endophthalmitis have been reported, including chronic metabolic diseases, immunosuppression, malignancy, intravenous drug abuse, long-term presence of an intracorporeal foreign body, and invasive surgery [ 13 14 15 16 ]. According to a worldwide systematic survey of endogenous bacterial endophthalmitis, diabetes was the most common predisposing medical condition, and liver abscess was the most common extraocular focus of infection [ 17 ].…”
Section: Endogenous Endophthalmitismentioning
confidence: 99%
“…Although it is caused by hematogenous spread, endogenous endophthalmitis tends to develop unilaterally, with the right eye more commonly affected, possibly due to the more proximal and direct arterial route from the heart to the right carotid artery. Several risk factors for endogenous endophthalmitis have been reported, including chronic metabolic diseases, immunosuppression, malignancy, intravenous drug abuse, long-term presence of an intracorporeal foreign body, and invasive surgery [ 13 14 15 16 ]. According to a worldwide systematic survey of endogenous bacterial endophthalmitis, diabetes was the most common predisposing medical condition, and liver abscess was the most common extraocular focus of infection [ 17 ].…”
Section: Endogenous Endophthalmitismentioning
confidence: 99%
“…Moreover, among patients with systemic Klebsiella infection, 7.3% were found to have EE caused by Klebsiella pneumoniae [ 9 ]. Another study found that a liver abscess in the right superior segment positive for K. pneumoniae infection was a significant risk factor for EE [ 10 ]. Thus, patients admitted for a liver abscess or systemic K. pneumoniae infection should be monitored closely for endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…KPLA infection exhibits a typical geographical distribution. The majority of cases have been reported from Taiwan, and cases have also been reported across Asia including Japan, Korea and Singapore . KPLA with endogenous spread was rarely reported in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…EKPE is now the commonest cause of endogenous endophthalmitis in Asia, with up to 9% prevalence in patients with KPLA . The incidence of metastatic spread is 100‐fold higher in Klebsiella sepsis compared to sepsis caused by other organisms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation